Team building proven strategies for improving team performance - Dyer, W. Gibb Jr. 1954-; Dyer, Jeffrey H.; Dyer, William G. (Jossey-Bass, 2013)
Now in its fifth edition, Team Building is a classic in the field of organization development. In this new edition, the authors strengthen the Four Cs framework that was introduced in the fourth edition and add a wealth of new illustrative examples, a chapter on the challenges of managing cross-functional teams, and a chapter on leading innovative teams in a competitive environment. To complement the text, the authors have developed two online assessments: one designed for use in the classroom with student teams and one designed for teams within organizations. For more information, please visit www.josseybass.com/go/dyerteamassessments. The fifth edition of Team Building provides the next generation of team leaders, team members, and team consultants with the knowledge and skills they need to create effective and high-functioning teams.